FENOMENA BRAIN ROT DALAM PERSPEKTIF AL-QUR’AN: STUDI QUR’AN TEMATIK TERHADAP DEGRADASI KOGNITIF DI ERA DIGITAL - Adam Mustaqim Jiddan; Muhammad Alif (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Advances in digital technology and social media have significantly changed the way people consume information. The ease of access to various types of digital content contributes to a phenomenon known as "brain rot," which is a condition of cognitive decline characterized by reduced cognitive abilities, critical thinking, and intellectual reflection, as well as increased dependence on digital content and entertainment. This phenomenon affects not only the cognitive aspect, but also the spiritual qualities of the individual. Therefore, this study aims to analyze the phenomenon of brain rot from the perspective of the Qur'an, examine verses related to cognitive decline, and discuss Qur'anic solutions in facing the challenges of the digital era. This research uses a qualitative methodology with reference to the type of library research and thematic interpretation (tafsir maudhu'i). The Qur'an and classical and contemporary tafsir books are primary sources of data, while scientific journals, academic books, literature on "brain rot", and digital literacy are secondary sources of data. Data analysis is carried out through data reduction, verse categorization, and thematic interpretation with respect to relevant Qur'anic concepts. The findings of this study show that the phenomenon of brain rot is related to the concepts of laghw (useless activity), lahw (negligent entertainment), ghaflah (negligence), and la ya'qilun (not using reason optimally). The Qur'an provides solutions through the use of tafakkur, tadabbur, tabayyun, and tazkiyatun nafs as a means to improve mental and spiritual well-being in the context of digital information. This research shows that the Qur'an has strong relevance in providing an epistemological and ethical foundation to overcome the phenomenon of "brain rot", so that digital literacy based on the principles of the Qur'an is very important in forming a critical, reflective, and noble society in the digital era.